Co-Creation Experience of Indonesian Gen Z in Mobile Commerce - Muhammad Iqbal Firdaus; Cynthia A. Utama; Gita Gayatri; Whony Rofianto (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2025)
Anchoring on the value of co-creation theories and stimulus-organism-response (S-O-R), the purpose of the study is to examine co-creation experience among Gen Z. First, the study aims to investigate the role of mobile commerce quality in driving Gen Z co-creation experience. Second, it seeks to understand the impact of a positive co-creation experience on the likelihood of engaging in E-WOM. An online survey was designed to collect 679 responses using purposive sampling from mobile commerce users. The data was analysed using PLS-SEM to test the hypotheses. The results demonstrate that mobile commerce quality and personal traits contribute to increased co-creation experience. In addition, the results indicate that E-WOM is determined by learning, personal, and hedonic experiences, which are influenced by content quality, visual appeal, social interaction, and propensity to interact online. The research provides insights for mobile commerce managers into increasing co-creation experience as the source of competitive advantage.